2020
DOI: 10.1007/s10163-019-00957-8
|View full text |Cite
|
Sign up to set email alerts
|

Sodium dodecyl sulfate improves the treatment of waste paper with rumen fluid at lower concentration but decreases at higher condition

Abstract: Rumen fluid has been applied to lignocellulosic biomass digest for methane production, and various feed supplements have been shown to improve ruminant digestion of lignocellulosic biomass. Therefore, we investigated the effects of sodium dodecyl sulfate (SDS) on the pretreatment of lignocellulosic biomass with rumen fluid and subsequent methane fermentation. SDS was mixed with rumen fluid at concentrations of 0.1, 0.2, 0.4, and 0.8 g/L. After SDS addition, the waste paper was pretreated with rumen fluid at 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Thus, we speculate that Lactobacillus , Bifidobacterium , and Atopobium utilized xylan metabolites (i.e., xylooligosaccharides and xylose) and produced VFAs, especially lactic acid, after 24 h. The relative abundances of protozoal and fungal genera decreased during treatment. We previously reported that the relative abundances of protozoal and fungal genera significantly decreased during the treatment of carboxymethyl cellulose with rumen fluid for 48 h (Takizawa et al ., 2020a,b,c), which was consistent with the present results. Entodinium caudatum , Entodinium exiguum , Epidinium caudatum , and Ophryoscolex purkynjei decrease in abundance when the pH decreases below 5.4, whereas they maintain their levels around pH 5.8 (Dehority, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, we speculate that Lactobacillus , Bifidobacterium , and Atopobium utilized xylan metabolites (i.e., xylooligosaccharides and xylose) and produced VFAs, especially lactic acid, after 24 h. The relative abundances of protozoal and fungal genera decreased during treatment. We previously reported that the relative abundances of protozoal and fungal genera significantly decreased during the treatment of carboxymethyl cellulose with rumen fluid for 48 h (Takizawa et al ., 2020a,b,c), which was consistent with the present results. Entodinium caudatum , Entodinium exiguum , Epidinium caudatum , and Ophryoscolex purkynjei decrease in abundance when the pH decreases below 5.4, whereas they maintain their levels around pH 5.8 (Dehority, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The dried pellets were solubilized in 1 ml of 2× sample buffer comprising 20% ( v / v ) glycerol, 4% ( w / v ) SDS, 0.01% ( w / v ) bromophenol blue, 0.125 M Tris‐HCl (pH 7.4), 10% ( v / v ) 2‐mercaptoethanol, 2 mM phenylmethylsulfonyl fluoride, and 1× proteinase inhibitor (Sigma‐Aldrich). SDS‐PAGE and zymography were conducted according to a previous study (Takizawa et al ., 2020a,b,c), with some modifications. Briefly, the supernatants were heated at 70°C for 20 min and immediately cooled on ice.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations